Intimate partner violence and associated factors among HIV positive women attending antiretroviral therapy clinics in Gondar city, Northwest Ethiopia - Amsal Seraw Alemie; Hedija Yenus Yeshita; Ejigu Gebeye Zeleke; Birye Dessalegn Mekonnen (BMC, 2023)
Abstract Introduction Intimate partner violence against women is a behavior within an intimate relationship that causes sexual, physical, or psychological harm to the women. It occurs among all socioeconomic, religious, and cultural groups in all settings, and affects the health of women, families, and the community at large. Determining the magnitude and determinants of intimate partner violence against HIV positive women could help to design preventive and control strategies. However, there is a dearth of information regarding the magnitude and determinants of intimate partner violence against HIV positive women in Ethiopia. Thus, this study aimed to assess the magnitude and associated factors of intimate partner violence against HIV positive women in Gondar city, Northwest Ethiopia. Method A facility-based cross-sectional study was carried out from February to May 2021 in selected public health facilities of Gondar city among 626 HIV positive women. A systematic random sampling technique was used to select study participants. Data were analyzed using Statistical Package of Social Science (SPSS) version 20 software. Bivariable and Multivariable logistic regression models were done. Adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to identify determinants of intimate partner violence. Statistical significance was considered at a p value < 0.05. Results The overall prevalence of intimate partner violence against HIV positive women within the last 12 months was 64.2% (95% CI 60.4, 68.2). Physical violence was the most common type (54.8%), followed by sexual (51.1%) and emotional (48.9%) violence. Intimate partner violence among HIV positive women was associated with women's age 19-24 (AOR = 0.13, 95% CI 0.02, 0.79), monthly income of 500-2500 (AOR = 6.5, 95% CI 1.72, 25.0), urban residence (AOR = 0.35, 95% CI 0.13, 0.91), partner drink alcohol (AOR = 2.14, 95% CI 1.42, 4.06), and a husband with no multiple sexual partners (AOR = 0.75, 95% CI 0.34, 0.94). Conclusion The result of this study revealed that intimate partner violence against HIV positive women was found to be high. Thus, protective measures that could increase the community's and women's awareness about the consequences of various forms of violence, and women empowerment are paramount. Priorities in programs of gender-based violence prevention should involve women from rural residences, older age, and males who consume alcohol.